100 Patella Tendon Regeneration Using Collagen Peptide And Collagen Sheet. (5th September 2014) - Suzuki, Daisuke; Ikeya, Motoshi; Fujie, Hiromichi; Ogura, Takayuki; Koyama, Yoichi; Nagoya, Satoshi; Yamashita, Toshihiko
Abstract : Introduction: Central one third of patella tendon is used autograft for the ACL reconstruction. Although the clinical result using the patellar autograft is relatively satisfied, the donor site has not been restored histologically for long time. 4 This study we tried to regenerate the patella tendon of rat using the collagen sheet (CS) and collagen peptide (CS). The regenerated patellar tendons were assessed mechanical properties, and were investigated type III collagen amount. Methods: collagen sheet The CS was purified porcine corium collagen. The collagen was solved acidic solution (3 mg/ml collagen density), incubated at 37°C for 24 hours, homogenized and separated centrifugation. Pellets of collagen were solved ethanol, filtered and dried sheeted. Collagen peptide: The CP is 500–1000 molecular weight, and was made from porcine corium collagen treated with proteases. 2 Operation: 24 Male Sprague Dawley (SD) rats were used. The rats were bilaterally resected central one third of patella tendon. One side was embedded CS, and half of the operated rats were administrated 0.1g CP for one month. The groups embedded and not embedded collagen sheet were noted CS + and CS -, and the groups administrated and not administrated collagen peptide were noted CP + and CP -, respectively. We, therefore, assessed the four types of the patella tendon, i.e., CP - /CS -, CP + /CS -, CP - /CS +, CP + /CS + . The rats were sacrificed at 4 week, 8 week, and 12 week. The patella tendon was harvested and measured mechanical properties using hand-made micro-testing machine. The amounts of type III collagen were also measured by SDS-PAGE. Results: There were no obvious differences between CP - /CS + and CP - /CS - group in micro- and macroscopically. There was neither significant difference in the mechanical properties. The each strength was increased as time passed. On the other hand, the ultimate tensile strength of group CP + /CS + at 4 week was 13.74 ± 2.66 MPa, and the group CP + /CS - was 12.89 ± 5.21 MPa, which is significantly larger than those of the CP - /CS + group (9.82 ± 4.16 MPa) and CP - /CS - group(11.64 ± 3.53 Mpa), respectively. The stiffness was also significantly larger than CP - groups. The amounts of type III collagen were increased as time passed in no CP - groups. The CP + groups of 4 week were reached the same level of CP - groups of 8–12 week of postoperative. Discussion: In the rat tendon injury model, embedding CS is not expected enough to effect of treatment by itself. 3 However, combined treatment of CS and CP showed mechanically better result for the tendon injury. Generally, type III collagen was appeared initial stage of injury, and was suggested to restore part of the physical tensile strength. 1 The administrated CP was suggested makes promote the production of type III collagen and it might be contributed to the elevation of the mechanical properties. References: 1 Dahlgren LA, et al . Am J Vet Res 2005;66:266–271 2 Nishihara T, Miyata T. Collagen Sympo . 1962;3:84 3 Suzuki D, et al. abstract of Jpn Jour Clin Biomech . 2012;39:161 [in Japanese] 4 Svensson M, et al . Am J Sports Med . 2007;35:301–306